2010
DOI: 10.4103/0970-4388.60480
|View full text |Cite
|
Sign up to set email alerts
|

Treatment effects produced by preorthodontic trainer appliance in patients with class II division I malocclusion

Abstract: The aim of the present study was to evaluate cephalometrically the treatment effects of preorthodontic trainer on dentoskeletal components in individuals showing class II division I malocclusion. This study comprised of 50 class II div. I patients (20 test patients and 30 controls) in the age group of 8-12 years. The test group was treated with a preorthodontic trainer for a period of 15 months. Standardized lateral cephalograms of both groups were taken before and after the treatment period. The cephalograms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 1 publication
7
6
0
Order By: Relevance
“…However, the mandibular molars showed more mesial movement than maxillary molar favoring class I relation. These findings were in agreement with other studies, whether for the T4K [13,14] or twin block appliance [5,11]. The justification for molar relation improvement was based on the action of both appliances that share the same concept of forcing the patient to close in class I relation, resulting in mandibular forward movement with slight maxillary restriction.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, the mandibular molars showed more mesial movement than maxillary molar favoring class I relation. These findings were in agreement with other studies, whether for the T4K [13,14] or twin block appliance [5,11]. The justification for molar relation improvement was based on the action of both appliances that share the same concept of forcing the patient to close in class I relation, resulting in mandibular forward movement with slight maxillary restriction.…”
Section: Discussionsupporting
confidence: 91%
“…The overjet reduction encountered by both appliances in this study was supported by many other studies in the literature, where Usumez et al [13], Dass and Reddy [14] reported a significant reduction in the overjet in children between 8-12 years over a mean period of 13 and 15 months, respectively, when using the T4K appliance compared to the untreated controls. Similar findings were reported for the twin block appliance [8,9,24].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…54 Correction of class II or III malocclusions achieved through use of functional orthodontic or orthopedic devices that aim to correct the OP inclination by seeking parallelism between it and Camper's plane and a bilaterally balanced VD and, as a consequence, bilaterally balanced PMFAs as well, has shown much more stable treatment results. 37,[65][66][67][68] Although the reference line that Coro at al 37 used in their report was the Frankfort's plane, they concluded that the POP shows significant correlation with jaw posture. The steeper the POP is, the more retrognathic and hyperdivergent the jaw posture is.…”
Section: Discussionmentioning
confidence: 99%
“…22 Class II corrections can be achieved with the preorthodontic trainer appliance, which appears to have mostly dentoalveolar effects with smaller but significant skeletal effects. 23…”
Section: Discussionmentioning
confidence: 99%